Investigation of Some Neuroinfectious Viral Agents in Turkish Cattle: First Detection and Molecular Characterization of Bovine Herpesvirus Type 5 (BoHV-5) - Can-Sahna, Kezban; Abayli, Hasan; Ilgin, Mehmet; Aksoy, Mehmet (Univ Agriculture, Fac Veterinary Science, 2024)
Neuroinfectious diseases in cattle, which result in significant economic losses and pose a serious threat to animal health, often go undiagnosed due to the challenge of identifying their underlying cause. In this study, a total of 180 brain samples from cattle with neurological symptoms were collected from various provinces in T & uuml;rkiye during 2021-2022. Viral nucleic acids were extracted, followed by PCR and RT-PCR assays targeting specific gene regions of BoHV-1, BoHV-5, OvHV-2, and BoAstV. BoHV-1 was detected in 7.22% (13/180) of the samples, BoHV-5 in 5.00% (9/180), and OvHV-2 in 0.55% (1/180). BoAstV, however, was not detected in any of the samples. Analysis of the gB gene region sequences revealed a high nucleotide identity (100%) between BoHV-1 strains from America, Israel, Sweden, and Italy, and BoHV-5 strains (S9 and S24) from Brazil. The OvHV-2 strain obtained from this study clustered within the OvHV-2.1 cluster along with some Asian strains (Iraq, Pakistan, Mongolia, India, Turkey). Studies focused on neuroinfectious diseases in cattle, especially those related to BoAstV and BoHV-5, are relatively scarce. This study represents one of the first investigations into the majority of neuroinfectious viruses in Turkish cattle, with the identification of BoHV-5 being reported for the first time here. It is anticipated that the data obtained will significantly contribute to our understanding of the pathogenesis and molecular epidemiology of these studied viruses.
Keywords: BoAstV; BoHV-1; BoHV-5; Meningoencephalitis; OvHV-2